Diseño de una roladora de láminas semiautomática, con rodillos de 60 cm de longitud, para láminas de hasta 4 mm de espesor, destinada a la empresa mecánica MEFUNJAR - Jaramillo Lapo, Giordano Andrés (2024)
The present graduation thesis showcases the design of a sheet metal rolling machine capable of handling steel sheets up to 4 millimeters in thickness. Its structure corresponds to a four-roller rolling machine, chosen for its advantages over other types. Its primary objective is to be a machine of small dimensions, targeting small and medium-sized metalworking industries, exemplified by the mechanical company MEFUNJAR. The process began with a literature search on machine design, focusing on transmission elements such as gears, bearings, shafts, keyways, etc. A calculation methodology was formulated to, primarily, determine the force required to roll a steel sheet of predetermined dimensions, in order to select the appropriate geared motor to power the machine, and to obtain the minimum diameter required for the upper roller of the machine, using the mechanical properties of the alloyed steel AISI 4140. Next, the gear transmission was designed, consisting of two straight-toothed cylindrical gears made of hardened steel with a 5 mm module. The keys transmitting torque to the gears were designed using cold-drawn AISI 1020 steel. Bearing selection followed the calculation methodology provided by FAG bearing manufacturers, the single-row deep groove ball bearings were chosen for each shaft, ensuring a dynamic stress factor recommended by the manufacturer. The selected motor to power the machine is a 1.5 hp single-phase worm-gear motor reducer, and its start and control are facilitated by contactors and pushbuttons. For the rolling machine's structure, ASTM A36 black steel with a thickness of 6 mm was chosen, ideal for welded or threaded joints. Key words: Steel cylinder, metalworking, motor reducer, gear, 3D model.